Bajki Biernata z Lublina i Ignacego Krasickiego – rzecz o przeciwległych biegunach bajkopisarstwa - Magryś, Roman (Dydaktyka Polonistyczna, 2015)
The article Bajki Biernata z Lublina i Ignacego Krasickiego – rzecz o przeciwległych biegunach bajkopisarstwa [The Fables by Biernat of Lublin and Ignacy Krasicki – The Issue Relating to the Opposite Ends of Fable Writing] discusses the problem of the Polish society in the 16th and 18th centuriespresented in the fables by the aforementioned.Basing on them, one can note that the Polish class society in the 16th century was more mobile. Then, it was possible to promote to a higher position owing to university education or other public services. Biernat’s fables put their trust in building a more egalitarian society, although the author is well aware of the gross social inequalities of the feudal system, which could be changed through revolution. The 18th century brings regression of ethics in public life,where corruption and lawlessness are present, and the serfs suffer considerable feudal oppression. The fables by Ignacy Krasicki reveal the mechanisms of the negative phenomena and social processes, having no illusions about fighting the existing evil. The author paints the Enlightenment period black, as traditional morality gave in to omnipresent selfishness.